Method for producing porous liquid crystal polymer sheet

By integrating liquid crystal polymer with inorganic compound kneeing and extracting inorganic compounds with supercritical fluids, the problem of difficult foaming agent kneeing in the production of high-melting liquid crystal polymer sheets is solved, and an efficient and reliable production process is achieved.

JP2025039102APending Publication Date: 2025-03-21NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145953
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when producing high-melting point liquid crystal polymer sheets, it is difficult to effectively knead the foaming agent, resulting in inefficient production efficiency of foamed liquid crystal polymer sheets.

Method used

The method of integrating liquid crystal polymer with inorganic compound kneeing is adopted, and the inorganic compound is extracted through supercritical fluid to produce efficient foam liquid crystal polymer sheets.

Benefits of technology

It realizes effective kneeing foaming agent under high melting point conditions, improves the production efficiency of foam liquid crystal polymer sheets, and ensures high quality and reliability of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039102000001_ABST
    Figure 2025039102000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a porous liquid crystal polymer that allows reliable kneading of a pore-forming agent with a liquid crystal polymer and enables reliable production of the porous liquid crystal polymer, even when a melting point of the liquid crystal polymer is high.SOLUTION: There is provided a method for producing a porous liquid crystal polymer sheet, comprising the steps for: producing a sheet of a composition comprising a liquid crystal polymer and an inorganic compound; and extracting the inorganic compound from the sheet using supercritical fluid.SELECTED DRAWING: Figure 1B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a porous liquid crystal polymer sheet, a method for producing a laminate, and a method for producing a wired circuit board. [Background technology]

[0002] A porous liquid crystal polymer sheet is obtained by making a liquid crystal polymer porous. As a method for making a liquid crystal polymer porous, for example, a method for producing a porous liquid crystal polymer has been proposed (see Patent Document 1), which includes a first step of kneading a liquid crystal polymer and a porogen to prepare a composition containing the liquid crystal polymer and the porogen, and a second step of extracting the porogen from the composition with a supercritical fluid, in which the mass reduction rate of the porogen at 230°C is 10% by mass or less. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2022 / 209618 Brochure Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 1 provides a method for producing a porous liquid crystal polymer, which can reliably knead a porosifying agent with a liquid crystal polymer and reliably produce a porous liquid crystal polymer. In this method, for example, a purine derivative, a bisphenol AF derivative, a pearl fluoropolyether derivative, a calixarene derivative, a dicarboxylic anhydride derivative, etc. are used as the porosifying agent. However, if the melting point of the porous liquid crystal polymer sheet is high, kneading may become difficult.

[0005] An object of the present invention is to provide a method for producing a porous liquid crystal polymer, which can reliably knead a porosifying agent together with a liquid crystal polymer and reliably produce a porous liquid crystal polymer even when the melting point of the liquid crystal polymer is high. A further object of the present invention is to provide a method for producing a laminate and a method for producing a wired circuit board using the method for producing the porous liquid crystal polymer. [Means for solving the problem]

[0006] That is, the present invention includes the following.

[0007] [1] A step of preparing a sheet of a composition containing a liquid crystal polymer and an inorganic compound; extracting the inorganic compound from the sheet with a supercritical fluid; A method for producing a porous liquid crystal polymer sheet, comprising the steps of: [2] The method for producing a porous liquid crystal polymer sheet according to [1], wherein the extracting step is carried out in the presence of an alcohol having 1 to 3 carbon atoms. [3] The method for producing a porous liquid crystal polymer sheet according to [2], wherein the solubility of the inorganic compound in the alcohol having 1 to 3 carbon atoms is 10 or more. [4] The method for producing a porous liquid crystal polymer sheet according to [1] or [2], further comprising a step of contacting the sheet with a solvent prior to the extracting step. [5] The method for producing a porous liquid crystal polymer sheet according to any one of [1] to [3], wherein the inorganic compound is an inorganic salt. [6] The method for producing a porous liquid crystal polymer sheet according to [5], wherein the inorganic salt is at least one of an alkali metal halide and an alkaline earth metal halide. [7] The method for producing a porous liquid crystal polymer sheet according to any one of [1] to [6], wherein the composition is obtained by kneading the liquid crystal polymer and the inorganic compound. [8] A method for producing a laminate having a porous liquid crystal polymer sheet and a metal layer in order in a thickness direction, comprising: [1] to [7], using the method for producing a porous liquid crystal polymer sheet according to any one of [1] to [7], A method for manufacturing a laminate. [9] A method for producing a wiring circuit board having a porous liquid crystal polymer sheet and a conductor layer in order in a thickness direction, comprising: [1] to [7], using the method for producing a porous liquid crystal polymer sheet according to any one of [1] to [7], A method for manufacturing a printed circuit board. Effect of the Invention

[0008] According to the present invention, a method for producing a porous liquid crystal polymer can be provided, which can reliably knead a porosifying agent together with a liquid crystal polymer even when the melting point of the liquid crystal polymer is high, and can reliably produce a porous liquid crystal polymer. Furthermore, according to the present invention, it is possible to provide a method for producing a laminate and a method for producing a wired circuit board using the above-mentioned method for producing a porous liquid crystal polymer. [Brief description of the drawings]

[0009] [Figure 1A] FIG. 1A is a process diagram for explaining one embodiment of a method for producing a porous liquid crystal polymer sheet (part 1). [Figure 1B] FIG. 1B is a process diagram for explaining one embodiment of the method for producing a porous liquid crystal polymer sheet (part 2). [Diagram 2] FIG. 2 is a schematic cross-sectional view of one embodiment of a laminate. [Diagram 3] FIG. 3 is a schematic cross-sectional view of one embodiment of a printed circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Method of manufacturing a porous liquid crystal polymer sheet) The method for producing a porous liquid crystal polymer sheet of the present invention includes a sheet preparation step and an extraction step. The method for producing a porous liquid crystal polymer sheet may include other steps, such as a solvent contact step.

[0011] A method for producing a porous liquid crystal polymer sheet 1, which is one embodiment of the method for producing a porous liquid crystal polymer of the present invention, will be described with reference to Figures 1A and 1B. This production method includes a sheet preparation step and an extraction step as essential steps. This production method also includes a solvent contact step as an optional step.

[0012] <Sheet manufacturing process> The sheet preparation step is a step of preparing a sheet of a composition containing a liquid crystal polymer and an inorganic compound.

[0013] <<Liquid crystal polymer>> The liquid crystal polymer is not limited. The liquid crystal polymer is a liquid crystal thermoplastic resin. Examples of the liquid crystal polymer include liquid crystal polyester, preferably aromatic liquid crystal polyester. The liquid crystal polymer is specifically described in, for example, JP 2020-147670 A and JP 2004-189867 A. The liquid crystal polymer may be a commercially available product. Examples of commercially available products include UENO LCP (registered trademark, hereinafter the same) 8100 series (low melting point type, manufactured by Ueno Pharmaceutical Co., Ltd.) and UENO LCP 5000 series (high melting point type, manufactured by Ueno Pharmaceutical Co., Ltd.). The UENO LCP 5000 series is preferable.

[0014] The melting point of the liquid crystal polymer is not limited. The melting point of the liquid crystal polymer is, for example, 200°C or higher, preferably 220°C or higher, more preferably 250°C or higher, and for example, 370°C or lower. The melting point of the liquid crystal polymer is determined by differential scanning calorimetry. In differential scanning calorimetry, the temperature rise rate is 10°C / min, and the liquid crystal polymer is heated in a nitrogen atmosphere, for example, in a range from 25°C to 400°C. In addition, if the liquid crystal polymer is a commercially available product, the catalog value of the commercially available product can be used as is. If the melting point of the liquid crystal polymer is equal to or lower than the above upper limit, the porous liquid crystal polymer sheet 1 is excellent in handleability and processability. If the melting point of the liquid crystal polymer is equal to or higher than the above lower limit, the porous liquid crystal polymer sheet 1 is excellent in heat resistance.

[0015] The glass transition temperature of the liquid crystal polymer is not limited. The glass transition temperature of the liquid crystal polymer is, for example, 80° C. or higher and, for example, 125° C. or lower. The glass transition temperature of the liquid crystal polymer is determined by differential scanning calorimetry performed at a heating rate of 10° C. / min.

[0016] <<Inorganic compounds>> The inorganic compound acts as a porosifying agent. The porosifying agent is a component dispersed in the liquid crystal polymer to make the liquid crystal polymer porous. Since the inorganic compound does not dissolve in the liquid crystal polymer, it undergoes phase separation from the liquid crystal polymer at the kneading temperature (described later). Phase separation includes the fact that the inorganic compound does not dissolve in the liquid crystal polymer and maintains a constant shape in the kneaded product.

[0017] When preparing a sheet of a composition containing a liquid crystal polymer and a porosifying agent, for example, the liquid crystal polymer and the porosifying agent are kneaded together. Inorganic compounds generally have a higher melting point than organic compounds, so that the porosity-inducing agent can be reliably kneaded together with the liquid crystal polymer even when the liquid crystal polymer has a higher melting point than when an organic compound is used as the porosity-inducing agent.

[0018] The inorganic compound is not particularly limited, but examples thereof include inorganic salts, inorganic oxides, inorganic nitrides, inorganic sulfides, etc. Among these, inorganic salts are preferred because they are easily extracted in the extraction step.

[0019] The inorganic salt may be anhydrous or hydrated, with the anhydrous being preferred. The inorganic salt is not particularly limited, but examples thereof include metal halides, metal nitrates, metal sulfates, and metal carbonates. Among these, metal halides are preferred because they are easily extracted in the extraction step. Examples of halogens in metal halides include fluorine, chlorine, bromine, and iodine. Among these, chlorine and bromine are preferred. The metal in the inorganic salt is not particularly limited, but an alkali metal or an alkaline earth metal is preferable. Examples of the alkali metal include lithium, sodium, potassium, rubidium, cesium, francium, etc. Among these, lithium, sodium, and potassium are preferred. Examples of alkaline earth metals include beryllium, magnesium, calcium, strontium, barium, and radium. Of these, calcium is preferred.

[0020] The metal halide is preferably at least one of an alkali metal halide and an alkaline earth metal halide. Examples of the alkali metal halide include lithium chloride, sodium chloride, potassium chloride, lithium bromide, sodium bromide, and potassium bromide. Examples of the alkaline earth metal halides include calcium chloride and calcium bromide.

[0021] The inorganic compound is usually kneaded in the form of a powder. The average particle size of the inorganic compound is not particularly limited, and can be appropriately determined depending on the degree of porosity, the thickness of the porous liquid crystal polymer sheet, and the like. The average particle size of the powdered inorganic compound is, for example, 0.001 mm to 0.8 mm, preferably 0.003 mm to 0.6 mm, and more preferably 0.005 mm to 0.4 mm. The average particle size can be measured by a laser diffraction / scattering type particle size distribution measuring device.

[0022] The melting point of the inorganic compound is preferably higher than the melting point (Tm) of the liquid crystal polymer, more preferably 10° C. or more higher than the melting point of the liquid crystal polymer, and particularly preferably 20° C. or more higher than the melting point of the liquid crystal polymer. The melting point of the inorganic compound is preferably, for example, equal to or lower than the melting point of the liquid crystal polymer +600°C. The melting point of the inorganic compound can be determined, for example, by the same method as that for measuring the melting point of the liquid crystal polymer. The temperature range for differential scanning calorimetry in measuring the melting point of the inorganic compound is, for example, 25°C to 1,000°C.

[0023] The blending ratio of the liquid crystal polymer and the inorganic compound (porosifying agent) is not limited. The blending ratio of the liquid crystal polymer and the inorganic compound is appropriately adjusted so that the resulting porous liquid crystal polymer sheet has a desired porosity P. Specifically, the percentage of the volume of the inorganic compound relative to the total volume of the liquid crystal polymer and the inorganic compound is, for example, 20 volume% or more, preferably 30 volume% or more, more preferably 40 volume% or more, and, for example, 90 volume% or less, preferably 80 volume% or less, more preferably 70 volume% or less. The percentage of the volume of the inorganic compound relative to the total volume of the liquid crystal polymer and the inorganic compound is calculated by conversion using specific gravity from the percentage of the mass of the inorganic compound relative to the total mass of the liquid crystal polymer and the inorganic compound.

[0024] The composition may further contain an additive. The additive is different from the porosifying agent. The additive may be, for example, a filler. The filler may be, for example, a hollow sphere. The hollow sphere may, for example, include a glass balloon. The hollow sphere is, for example, described in JP 2004-189867 A.

[0025] If the composition contains hollow spheres, a porous liquid crystal polymer sheet 1 having a high porosity P can be produced.

[0026] On the other hand, if the composition does not contain hollow spheres, the porous liquid crystal polymer sheet 1 can be prevented from becoming brittle.

[0027] The composition can be obtained, for example, by kneading a liquid crystal polymer and an inorganic compound.

[0028] The kneading temperature is not limited, and is, for example, within the range of the melting point of the liquid crystal polymer ±30°C (that is, 250°C or more and 310°C or less when the melting point of the liquid crystal polymer is 280°C), preferably within the range of the melting point of the liquid crystal polymer ±20°C, more preferably within the range of the melting point of the liquid crystal polymer ±10°C, and even more preferably within the range of the melting point of the liquid crystal polymer ±5°C. The kneading temperature during kneading is, for example, the melting point of the inorganic compound (porous agent) minus 5° C. or lower, preferably the melting point of the porous agent minus 10° C. or lower, and more preferably the melting point of the porous agent minus 20° C. or lower. In other words, the melting point of the inorganic compound (porous agent) is, for example, 5° C. or higher than the kneading temperature, preferably 10° C. or higher than the kneading temperature, and more preferably 20° C. or higher than the kneading temperature.

[0029] In the sheet preparation step, the composition containing the liquid crystal polymer and the inorganic compound is formed into a sheet. Methods for forming the composition into a sheet include, for example, pressing, extrusion, and injection molding. Pressing is preferred, and heat pressing is more preferred. The temperature of the heat press is not limited. Specifically, the temperature of the heat press is, for example, 200° C. or higher and 400° C. or lower. In addition, the temperature of the heat press is preferably, for example, 5° C. or higher than the melting point of the liquid crystal polymer. The pressing pressure is, for example, 1 MPa or more, preferably 4 MPa or more, and for example, 20 MPa or less, preferably 10 MPa or less. Thereby, a nonporous sheet 3 containing a liquid crystal polymer and an inorganic compound (porous agent) is obtained.

[0030] There is no particular limitation on the thickness of the nonporous sheet 3. For example, the thickness of the nonporous sheet 3 is appropriately set according to the target thickness of the porous liquid crystal polymer sheet 1.

[0031] <Extraction process> The extraction step is a step of extracting the inorganic compound serving as the porosity agent from the sheet with a supercritical fluid. Specifically, the porosity agent in the nonporous sheet 3 is extracted with the supercritical fluid. For example, as shown in FIG. 1B, the extraction step uses a supercritical apparatus 10. The supercritical apparatus 10 includes a pressure vessel 11 and a circulation device (not shown). The pressure vessel 11 contains a supercritical fluid 15 and allows the supercritical fluid 15 to flow therethrough. The circulation device circulates the supercritical fluid 15 through the pressure vessel 11. The circulation device is also provided with a recovery device. The recovery device removes the porosifying agent extracted into the supercritical fluid 15.

[0032] <<Supercritical fluid 15>> There is no limitation on the type of supercritical fluid 15. Examples of the supercritical fluid 15 include supercritical carbon dioxide and supercritical nitrogen. From the viewpoint of production costs, the supercritical fluid 15 is preferably supercritical carbon dioxide.

[0033] <<Entrainer>> An entrainer may be added to the supercritical fluid 15. In other words, the extraction process may be carried out in the presence of an entrainer. The entrainer is added to the supercritical fluid 15 in order to increase the efficiency of extraction of the porosifying agent by the supercritical fluid 15. Examples of the entrainer include water, alcohol compounds, ketone compounds, ester compounds, aromatic compounds, long-chain alkyl compounds, and aprotic amide compounds. These can be used alone or in combination.

[0034] The alcohol compound may, for example, be an alcohol having 1 to 3 carbon atoms. Examples of the alcohol having 1 to 3 carbon atoms include methanol, ethanol, and propanol. Examples of the ketone compound include acetone and methyl ethyl ketone. Examples of the ester compound include methyl acetate, ethyl acetate, and propyl acetate. Examples of aromatic compounds include benzene, toluene, and xylene. Examples of long chain alkyl compounds include pentane, hexane, and heptane. Examples of aprotic amide compounds include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAC). As the entrainer, preferably, an alcohol compound, an ester compound, or an aprotic amide compound is used.

[0035] The solubility of the inorganic compound in the entrainer is not particularly limited, but is, for example, 5 or more, preferably 10 or more, more preferably 15 or more, and is, for example, 50 or less, preferably 45 or less, and more preferably 40 or less. When the solubility of the inorganic compound in the entrainer is high, the extraction rate is high and the amount of extraction is large, which makes the entrainer more porous. The solubility of an inorganic compound in an entrainer can be determined, for example, as follows. The solubility is measured in an environment of 25°C. (1): Add 10 g of methanol (entrainer, 25°C) to a 30 mL glass bottle. (2): Next, add the porosifier to a 30 mL glass bottle so that the solids concentration becomes 5 wt %. (3): Next, mix thoroughly by shaking the glass bottle by hand for 3 minutes. (4): Next, visually check whether any residual porosifying agent remains. (5): When no residual porosity agent is found by visual inspection, add more porosity agent to the 30 mL glass bottle so that the solids concentration is increased by 5 wt%. (6): Next, mix thoroughly by shaking the glass bottle by hand for 3 minutes. (7): Visually check for any residual porosifying agent. (8) If no residual porosifying agent is found by visual inspection, steps (5) to (7) are repeated. After carrying out the above steps, the maximum solid content concentration at which no residual porosifying agent is visually observed is taken as the solubility in the entrainer. For example, if no residual porosifier is visible to the naked eye at a solids concentration of 10 wt%, but residual porosifier is visible to the naked eye at a solids concentration of 15 wt%, the solubility of the inorganic compound in the entrainer is set to "10".

[0036] The mixing ratio of the entrainer is appropriately set. Specifically, the mixing flow rate of the entrainer is, for example, 0.1 mL / min or more, preferably 1 mL / min or more, and for example, 20 mL / min or less, preferably 5 mL / min or less, relative to a circulation flow rate of the supercritical fluid of 100 mL / min. The mixing ratio of the entrainer relative to the supercritical fluid used is, for example, 5.0 wt% or more, or preferably 10 wt% or more, and for example, 50 wt% or less, or preferably 40 wt% or less.

[0037] The nonporous sheet 3 is placed in a pressure vessel 11. Then, in the supercritical apparatus 10, a supercritical fluid 15 is made to flow into the pressure vessel 11. Then, the supercritical fluid 15 is circulated by a circulation device (not shown). As a result, the supercritical fluid 15 comes into contact with the nonporous sheet 3.

[0038] Then, first, the supercritical fluid 15 outside the nonporous sheet 3 is impregnated into the nonporous sheet 3. That is, the supercritical fluid 15 penetrates into the nonporous sheet 3. Then, the above-mentioned supercritical fluid 15 returns to the outside of the nonporous sheet 3 while dissolving the porosifying agent. As a result, the porosifying agent is extracted from the nonporous sheet 3 by the supercritical fluid 15.

[0039] The conditions of the extraction step are not limited. The temperature of the supercritical fluid 15 is, for example, higher than the glass transition temperature of the liquid crystal polymer described above. The temperature of the supercritical fluid 15 is, for example, at least 10°C higher, preferably at least 30°C higher, more preferably at least 50°C higher, and even more preferably 70°C higher than the glass transition temperature of the liquid crystal polymer described above. As described above, if the temperature of the supercritical fluid 15 is higher than the glass transition temperature of the liquid crystal polymer, the extraction efficiency of the supercritical fluid 15 in the extraction step can be increased. Therefore, a porous liquid crystal polymer sheet 1 with a high porosity P can be produced. The temperature of the supercritical fluid 15 is, for example, 40°C or higher, preferably 75°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, particularly preferably 150°C or higher, and most preferably 170°C or higher, and, for example, 200°C or lower, preferably 190°C or lower, and more preferably 180°C or lower.

[0040] The pressure of the supercritical fluid 15 is, for example, 10 MPa or more, preferably 20 MPa or more, and for example, 35 MPa or less, preferably 30 MPa or less.

[0041] The extraction time is, for example, 20 minutes or more, preferably 1 hour or more, more preferably 3 hours or more, even more preferably 5 hours or more, particularly preferably 8 hours or more, most preferably 10 hours or more, and, for example, 100 hours or less, preferably 48 hours or less, more preferably 24 hours or less. If the extraction time is not less than the above-mentioned lower limit, the extraction efficiency of the supercritical fluid in the extraction step can be increased, and a porous liquid crystal polymer sheet 1 having a high porosity P can be produced. If the extraction time is not more than the above-mentioned upper limit, the tact time can be shortened, and production efficiency can be improved.

[0042] The extraction rate of the porosifying agent from the sheet is not particularly limited, but is preferably 5% or more, more preferably 10% or more, and particularly preferably 20% or more. The extraction rate of the porosifying agent from the sheet is not particularly limited, but is preferably 100% or less. The higher the extraction rate, the higher the porosity. In this respect, the extraction rate is preferably 5% or more. The method for measuring the extraction rate will be described in the Examples below.

[0043] The pressure in the pressure vessel 11 is reduced while removing the supercritical fluid 15 inside the pressure vessel 11. Specifically, the pressure in the pressure vessel 11 is returned to atmospheric pressure. The rate of pressure reduction is not limited. For example, the rate of pressure reduction is adjusted so as to suppress foaming caused by the supercritical fluid 15 impregnated in the nonporous sheet 3. At this time, the pressure vessel 11 may be heated or may not be heated. The heating temperature is the same as the temperature of the supercritical fluid in the extraction, and is, for example, 40°C or higher, preferably 75°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, particularly preferably 150°C or higher, most preferably 170°C or higher, and, for example, 200°C or lower, preferably 190°C or lower, more preferably 180°C or lower. The heating time is, for example, 10 minutes or more and 3 hours or less. That is, in one example, the heating temperature is kept the same as the temperature of the supercritical fluid in the extraction until the pressure in the pressure vessel 11 is returned to atmospheric pressure, and after the pressure in the pressure vessel 11 is returned to atmospheric pressure, the heating temperature may be maintained or heating may be stopped.

[0044] As a result of the above, a plurality of pores 2 are formed in place of the porosity-forming agent that had been impregnated in the nonporous sheet 3. In this way, the porous liquid crystal polymer sheet 1 is manufactured.

[0045] <Solvent contact step> The method for producing a porous liquid crystalline polymer sheet may include a step of contacting the sheet with a solvent prior to the extracting step. By contacting the sheet with a solvent before the extraction step, the inorganic compounds exposed on the surface of the sheet can be removed from the sheet. The sheet from which the inorganic compounds have been removed from the surface becomes soft and has excellent handleability. For example, when a long sheet is rolled up, the sheet is less likely to crack. The inorganic compounds exposed at the surface of the sheet are removed from the surface of the sheet, for example, by dissolving them in a solvent.

[0046] The method for contacting the sheet with the solvent is not particularly limited, and examples thereof include a method in which the sheet is immersed in the solvent. The temperature of the solvent when the sheet is brought into contact with the solvent is not particularly limited, and is, for example, 15° C. or higher, preferably 20° C. or higher, and for example, 80° C. or lower, preferably 60° C. or lower. The time for which the sheet is contacted with the solvent is not particularly limited, and is, for example, 1 minute or more, preferably 5 minutes or more, and for example, 1 hour or less, preferably 30 minutes or less.

[0047] The solvent is not particularly limited, and examples thereof include water and organic solvents. Examples of the organic solvent include alcohol compounds, ketone compounds, ester compounds, aromatic compounds, long-chain alkyl compounds, aprotic amide compounds, etc. Specific examples of these include those listed in the above description of the entrainer. Among these, water and alcohol compounds are preferred, and water is more preferred, in that they easily dissolve inorganic compounds.

[0048] The porous liquid crystal polymer sheet 1 has a thickness and a sheet shape. The sheet shape includes a film shape. The porous liquid crystal polymer sheet 1 extends in a planar direction. The planar direction is perpendicular to the thickness direction. The porous liquid crystal polymer sheet 1 has a large number of fine pores (air pores). The air bubble structure of the porous liquid crystal polymer sheet 1 may be, for example, a closed air bubble structure, an open air bubble structure, or a semi-closed semi-open air bubble structure. From the viewpoint of circuit board processability, a closed cell structure is preferable because, for example, when a circuit board is manufactured, if holes are made with a drill or laser and then plating is performed, the plating solution may penetrate through the pores exposed by the holes, causing the conductor layer to precipitate (plating solution immersion), or when a porous sheet is bonded to a copper foil, the holes may be crushed by hot pressing (press resistance).

[0049] The closed-cell structure of the porous liquid crystal polymer sheet can be confirmed by using a penetrant liquid such as that used in the penetrant inspection test specified in JIS (JIS Z 2343-1, etc.). Preferably, the contact angle with respect to the polymer surface is 25° or less, the viscosity is 2.4 mm. 2 / s (37.8°C). That is, the porous liquid crystal polymer sheet is cut almost perpendicularly to the surface to expose the porous cross section, and the cross section is immersed in a penetrant such as a red penetrant for 5 minutes, after which the immersion length (the distance the penetrant has penetrated from the cross section) is measured. If the immersion length is 500 μm or less, or even 300 μm or less, the structure of the porous liquid crystal polymer sheet can be said to be a closed-cell structure.

[0050] The thickness of the porous liquid crystal polymer sheet 1 is not particularly limited, but is, for example, 0.01 mm to 1 mm, more preferably 0.05 mm to 1 mm, and particularly preferably 0.1 mm to 1 mm.

[0051] <Porosity P> The porosity P of the porous liquid crystal polymer sheet 1 is, for example, 1% or more, preferably 1.5% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 15% or more. The upper limit of the porosity P of the porous liquid crystal polymer sheet 1 is not limited. The upper limit of the porosity P of the porous liquid crystal polymer sheet 1 is, for example, 60%, preferably 50%. The method for measuring the porosity of the porous liquid crystal polymer sheet will be described in the examples below. When the porosity cannot be determined by the method described in the Examples below, the porosity may be determined by the following methods (1) to (3). (1) The dielectric constant of the porous liquid crystal polymer sheet (Dk 0 The measurement is carried out by the method described in the Examples below. (2) The relative dielectric constant (Dk 1 ) is required. Dk 1 is calculated from the volume ratio of each component other than air in the porous liquid crystal polymer sheet and the relative dielectric constant, using the Maxwell-Garnett model. (3) Dielectric constant (Dk 0 ) and relative dielectric constant (Dk 1 ) and the volume fraction of air (porosity) in the porous liquid crystal polymer sheet is calculated using the Maxwell-Garnett model. The volume ratio of each component other than air in the porous liquid crystal polymer sheet can be calculated, for example, using the calculation results of the amount of the porosifying agent in the porous liquid crystal polymer sheet, the calculation results of the extraction rate, etc.

[0052] <Dielectric constant> The relative dielectric constant of the porous liquid crystal polymer sheet 1 at 10 GHz is, for example, less than 3.10, preferably 2.90 or less, more preferably 2.80 or less, and even more preferably 2.75 or less. If the relative dielectric constant of the porous liquid crystal polymer sheet 1 is equal to or less than the above-mentioned upper limit, the porous liquid crystal polymer sheet has low dielectric constant. The lower limit of the relative dielectric constant of the porous liquid crystal polymer sheet at 10 GHz is not limited. For example, the lower limit of the relative dielectric constant of the porous liquid crystal polymer sheet at 10 GHz is 1.00. The method for measuring the relative dielectric constant of the porous liquid crystal polymer sheet will be described in the following examples.

[0053] <Dielectric tangent> The dielectric loss tangent of the porous liquid crystal polymer sheet 1 at 10 GHz is, for example, 0.0025 or less, preferably 0.0020 or less, more preferably 0.0010 or less, further preferably 0.00070 or less, and particularly preferably 0.00060 or less. If the dielectric loss tangent of the porous liquid crystal polymer sheet 1 is equal to or less than the upper limit, the porous liquid crystal polymer sheet has low dielectric constant. The lower limit of the dielectric loss tangent of the porous liquid crystal polymer sheet at 10 GHz is not limited. For example, the lower limit of the dielectric loss tangent of the porous liquid crystal polymer sheet at 10 GHz is 0.00000. The method for measuring the dielectric loss tangent of the porous liquid crystal polymer sheet will be described in the following examples.

[0054] <Applications of Porous Liquid Crystal Polymer Sheet 1> There is no limitation on the use of the porous liquid crystal polymer sheet 1. Examples of the use of the porous liquid crystal polymer sheet 1 include an insulating layer of a wiring circuit board and an antenna substrate for wireless communication.

[0055] (Laminate manufacturing method) The method for producing a laminate of the present invention is a method for producing a laminate having a porous liquid crystal polymer sheet and a metal layer in this order in the thickness direction. The method for producing a laminate includes the step of producing a porous liquid crystal polymer sheet using a method for producing a porous liquid crystal polymer sheet. The laminate may further include, for example, an adhesive layer. In the laminate, the porous liquid crystal polymer sheet is the insulating layer.

[0056] <Metal layer> The metal layer has a sheet (plate) shape. The material of the metal layer is not particularly limited, and examples thereof include copper, iron, silver, gold, aluminum, nickel, and alloys thereof (stainless steel, bronze), etc. Copper is preferable.

[0057] The thickness of the metal layer is, for example, 0.1 μm or more, preferably 1 μm or more, and for example, 100 μm or less, preferably 50 μm or less.

[0058] <Adhesive layer> The adhesive layer has a sheet shape extending along the surface direction, for example, on one surface in the thickness direction of the porous liquid crystal polymer sheet.

[0059] The material of the adhesive layer is not particularly limited, and various types of adhesives such as hot melt adhesives and thermosetting adhesives can be used, and specific examples include acrylic adhesives, epoxy adhesives, silicone adhesives, etc. Preferably, an acrylic adhesive is used.

[0060] The thickness of the adhesive layer is, for example, 2 μm or more, preferably 5 μm or more, and for example, 50 μm or less, preferably 25 μm or less.

[0061] The laminate is used for various purposes, for example, and is preferably used for manufacturing high-frequency antennas and high-speed transmission boards (such as high-speed transmission FPCs) that comply with the fifth generation (5G) standards. Specifically, the laminate is used as a substrate material for high-frequency antennas and high-speed FPCs.

[0062] As shown in FIG. 2, one example of the laminate includes a porous liquid crystal polymer sheet 1 and a metal layer 51 in this order toward one side in the thickness direction. In addition, in FIG. 2 and FIG. 3 described later, the pores in the porous liquid crystal polymer sheet 1 are omitted.

[0063] (Method of manufacturing a printed circuit board) The method for producing a wired circuit board of the present invention is a method for producing a wired circuit board having a porous liquid crystal polymer sheet and a conductor layer in this order in the thickness direction. The method for producing a wired circuit board includes a step of producing a porous liquid crystal polymer sheet by using a method for producing a porous liquid crystal polymer sheet. In the wiring circuit board, the porous liquid crystal polymer sheet is an insulating layer.

[0064] The wired circuit board has, for example, wiring as a conductor layer. Examples of the wiring include signal wiring, antenna wiring, ground wiring, etc. The wiring can be formed, for example, by patterning a metal layer by photolithography (for example, a subtractive method).

[0065] An example of a printed circuit board will be described with reference to the drawings. FIG. 3 is a schematic cross-sectional view of one embodiment of the wired circuit board of the present invention. The wiring circuit board 200 shown in Fig. 3 extends in a planar direction. The wiring circuit board 200 has a sheet shape. The wiring circuit board 200 includes a porous liquid crystal polymer sheet 1 and a conductor layer 52 in this order toward one side in the thickness direction. The conductor layer 52 contacts one surface in the thickness direction of the porous liquid crystal polymer sheet 1. The conductor layer 52 has a predetermined wiring pattern. The printed circuit board 200 shown in FIG. 3 can be produced, for example, in the following manner. First, a laminate 100 shown in FIG. 2 is prepared. Next, the metal layer 51 of the laminate 100 shown in FIG. 2 is patterned by photolithography to form a conductor layer 52 on the porous liquid crystal polymer sheet 1. In a variant, the porous liquid crystal polymer may have a bulk form, i.e., a non-porous bulk body containing the liquid crystal polymer and an inorganic compound (porogen) is prepared, and a porous liquid crystal bulk body is produced in the extraction process.

[0066] In a modified example, the porous liquid crystal polymer sheet 1 after the extraction step can be further thinned. Methods for thinning the porous liquid crystal polymer sheet 1 include, for example, pressing, stretching, and rolling. From the viewpoint of the accuracy of adjusting the thickness of the porous liquid crystal polymer sheet 1 obtained as a product, pressing is preferably used.

[0067] The modified wired circuit board includes a conductor layer, an insulating layer, and another conductor layer in this order toward one side in the thickness direction. The insulating layer is made of the porous liquid crystal polymer sheet described above. The two conductor layers are disposed on one side and the other side in the thickness direction of the insulating layer, respectively, and have a predetermined wiring pattern. EXAMPLES

[0068] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples and comparative examples.

[0069] <Example 1> <<First step>> A composition was prepared by kneading 80 parts by volume of UENO LCP A5000 (melting point 280°C) manufactured by Ueno Pharmaceutical Co., Ltd. as a liquid crystal polymer and 20 parts by volume of sodium bromide (powder, manufactured by Tokyo Chemical Industry Co., Ltd., melting point 747°C) as a porosifying agent using a Labo Plastomill (model number: 100C100) manufactured by Toyo Seiki Co., Ltd. The temperature during kneading was 340°C, and the rotation speed of the screw in the kneading device was adjusted to 30 rpm (revolutions per minute).

[0070] Next, a non-porous sheet having a thickness of 150 μm was produced from the kneaded product using a manual hydraulic vacuum press (model number: 11FD) manufactured by Imoto Manufacturing Co., Ltd. The temperature in the press was 340° C., and the pressure was 4 MPa.

[0071] <<Second process>> The nonporous sheet was immersed in water to extract the porosifying agent scattered on the surface of the nonporous sheet. The water temperature was 25° C., and the immersion time (extraction time) was 10 minutes.

[0072] <<3rd process>> Kobe Steel Air Tech "CO 2 Using a "supercritical fluid experimental apparatus," the porosifying agent was extracted from the sheet obtained in the second step using supercritical carbon dioxide as the supercritical fluid. Methanol was used as the entrainer (the amount of entrainer used was 10 wt% relative to the amount of carbon dioxide used in the treatment). The temperature of the supercritical carbon dioxide in the third step was 150°C, the pressure of the supercritical carbon dioxide was 30 MPa, and the impregnation time (extraction time) was 180 minutes.

[0073] <<Step 4>> While removing the supercritical carbon dioxide from the pressure vessel, the pressure in the pressure vessel was lowered to atmospheric pressure and heating was stopped, thereby obtaining a porous liquid crystal polymer sheet (porous sheet) having a thickness of 150 μm.

[0074] <Example 2> A porous liquid crystal polymer sheet (porous sheet) was obtained in the same manner as in Example 1, except that the porosifying agent in Example 1 was changed to calcium chloride (powder, manufactured by Fujifilm Wako Pure Chemical Industries, melting point 772° C.).

[0075] <Example 3> A porous liquid crystal polymer sheet (porous sheet) was obtained in the same manner as in Example 1, except that the porosity-producing agent in Example 1 was changed to lithium chloride (powder, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., melting point 613° C.).

[0076] <Example 4> A porous liquid crystal polymer sheet (porous sheet) was obtained in the same manner as in Example 3, except that the blending ratio of lithium chloride was changed to 30 parts by volume relative to 70 parts by volume of the liquid crystal polymer.

[0077] <Example 5> A porous liquid crystal polymer sheet (porous sheet) was obtained in the same manner as in Example 3, except that the blending ratio of lithium chloride was changed to 60 parts by volume relative to 40 parts by volume of the liquid crystal polymer.

[0078] <Comparative Example 1> In Example 1, sodium bromide was changed to caffeine (powder, melting point 238° C.). In Example 1, the second step was not carried out. In the third step of Example 1, no entrainer was used. In the third step of Example 1, the pressure of the supercritical carbon dioxide was changed to 25 MPa. Except for these changes, the porous liquid crystal polymer sheet was produced in the same manner as in Example 1. However, since the kneading temperature was higher than the melting point of caffeine, the caffeine powder volatilized during kneading and did not remain in the liquid crystal polymer. Therefore, the formation of holes could not be confirmed in the obtained liquid crystal polymer sheet.

[0079] <Solubility in entrainer> The solubility of the inorganic compound (porosifying agent) in the entrainer was determined as follows. The results are shown in Table 1. The solubility was measured in an environment of 25°C. (1): 10 g of methanol (entrainer, 25°C) was placed in a 30 mL glass bottle. (2): Next, the porosifier was added to a 30 mL glass bottle so that the solid concentration was 5 wt %. (3): Next, the glass bottle was shaken by hand for 3 minutes to thoroughly mix the mixture. (4) Next, the presence or absence of any remaining porosifying agent was confirmed by visual inspection. (5) When no residual porosity agent was found by visual inspection, more porosity agent was added to the 30 mL glass bottle so that the solids concentration was increased by 5 wt%. (6): Next, the glass bottle was shaken by hand for 3 minutes to thoroughly mix the mixture. (7): The presence or absence of any residual porosifying agent was confirmed by visual inspection. (8) When no residual porosifying agent was found by visual inspection, steps (5) to (7) were repeated. After carrying out the above steps, the maximum solid content concentration at which no residual porosifying agent was visually observed was determined as the solubility in the entrainer. For example, if no residual porosifier is visible at a solids concentration of 10 wt%, but residual porosifier is visible at a solids concentration of 15 wt%, the solubility of the inorganic compound in the entrainer is determined to be "10".

[0080] <Extraction rate> The extraction rate was calculated from the following formula: The results are shown in Table 1. Extraction rate [%]=100×{(M i -M p ) / M s} M i : Mass of non-perforated sheet M p : Mass of perforated sheet M s : Mass of porosifying agent in raw material

[0081] <Dielectric constant and dielectric loss tangent> The dielectric constant (Dk) and dielectric loss tangent (Df) of the liquid crystal polymer sheet at 10 GHz were measured using a "10 GHz SPDR resonator" manufactured by QWED Co., Ltd., in accordance with the SPDR method (split post dielectric resonance method) in accordance with ASTM D150. The results are shown in Table 1.

[0082] [Table 1] The blending amounts (parts by volume) in Table 1 are the blending amounts (parts by volume) when the total amount of the liquid crystal polymer and the porosifying agent is taken as 100 parts by volume. [Explanation of symbols]

[0083] 1. Porous liquid crystal polymer sheet 2. Stoma 3. Non-porous sheet 10 Supercritical device 11 Pressure vessels 15 Supercritical fluid 51 Metal layer 52 Conductor layer 100 Laminate 200 Wiring circuit board

Claims

1. A step of preparing a sheet of a composition containing a liquid crystal polymer and an inorganic compound; extracting the inorganic compound from the sheet with a supercritical fluid; A method for producing a porous liquid crystal polymer sheet, comprising the steps of:

2. 2. The method for producing a porous liquid crystal polymer sheet according to claim 1, wherein the extracting step is carried out in the presence of an alcohol having 1 to 3 carbon atoms.

3. 3. The method for producing a porous liquid crystal polymer sheet according to claim 2, wherein the solubility of the inorganic compound in the alcohol having 1 to 3 carbon atoms is 10 or more.

4. The method for producing a porous liquid crystalline polymer sheet according to claim 1 , further comprising the step of contacting the sheet with a solvent prior to the step of extracting.

5. The method for producing a porous liquid crystal polymer sheet according to claim 1 , wherein the inorganic compound is an inorganic salt.

6. 6. The method for producing a porous liquid crystal polymer sheet according to claim 5, wherein the inorganic salt is at least one of an alkali metal halide and an alkaline earth metal halide.

7. The method for producing a porous liquid crystal polymer sheet according to claim 1 , wherein the composition is obtained by kneading the liquid crystal polymer and the inorganic compound.

8. A method for producing a laminate having a porous liquid crystal polymer sheet and a metal layer in order in a thickness direction, comprising: The method for producing a porous liquid crystal polymer sheet according to any one of claims 1 to 7 includes a step of producing the porous liquid crystal polymer sheet. A method for manufacturing a laminate.

9. A method for producing a wiring circuit board having a porous liquid crystal polymer sheet and a conductor layer in order in a thickness direction, comprising: The method for producing a porous liquid crystal polymer sheet according to any one of claims 1 to 7 includes a step of producing the porous liquid crystal polymer sheet. A method for manufacturing a printed circuit board.

Citation Information

Patent Citations

  • Method for producing porous liquid crystal polymer and porosity-imparting agent

    WO2022209618A1